(untitled) (Research, Society and Development, 2020)
This study aims to highlight the advances and challenges faced by Brazilian society in the face of the exploitation of child labor after the implementation of the Statute of the Child and Adolescent -ECA. Bibliographic and field research of a qualitative nature was used. We analyzed data from the National Household Sample Survey (PNAD) of 2015 on this social issue, putting on the agenda the gender and region that most predominates child labor, as well as documentary research through the analysis of data from the Specialized Reference Center for Social Assistance (CREAS) of the city of Teresina- PI in 2016. Most records of child labor by sex registered by PNAD in the year 2015, 66% are male and 34% female. In CREAS Teresina- PI, the male sex 55% and female 45%. The highest number of children per age group performing some work activity is between 15 and 17 years. About the area, 64% were rural and 36% urban. The challenges observed were: to overcome the cultural issue; the disarticulation of the policies of confrontation, and the advances in the confrontation of child labor, with the recognition of children and adolescents as subjects of rights as well as full-time schools. And the importance of putting ECA into practice, thus guaranteeing integral protection to all children and adolescents, giving them education, health, sports, leisure and especially dignity, made possible through public policies.